PERAN KEPUASAN KONSUMEN DALAM MEMEDIASI PENGARUH EXPERIENTAL MARKETING TERHADAP LOYALITAS KONSUMEN - Dewanthi, Astya; Wulandari K., Ni Made (E-Jurnal Manajemen; Vol 6 No 1 (2017), 2017)
The purpose of this study was to determine the influence of experiential marketing on consumer loyalty mediated by customer satisfaction. This research was conducted at Nirvana Beach Corner Dive & Watersport Tanjung Benoa Bali. The size of the sample taken 155 consumer respondents, with non-probability sampling method in the form of purposive sampling. Data analysis technique used is path analysis and test Sobel. The results of this study indicate that 1) Experiental marketing positive and significant impact on customer satisfaction; 2) Consumer Satisfaction positive and significant impact on the Customer Loyalty; 3) Marketing Experiental positive and significant impact on the Customer Loyalty; 4) Role of Customer Satisfaction is significantly mediates the effects of Experiental Marketing on Consumer Loyalty. The implication of this research is the company capable of reviewing the aspects of Experiental Marketing and Customer Satisfaction for both these variables may affect the company's Consumer Loyalty
Keywords: Experiental Marketing, Consumer Satisfaction, Consumer Loyalty